A one year study on changes in flexibility and stability characteristics in elite golfers - Parker, J.; Olsson, C.; Brorsson, S. (Högskolan i Halmstad, 2011)
The results from this study show that training strategies can lead to improved flexibility and stability in golfers during the off season, however maintaining these improvements, particularly flexibility, during the in-season is not as easy. Decreased flexibility on the left side leads to reduced ROM to manage deceleration of forces produced in the golf swing that probably lead to an increased risk of injury. Significant improvements can be made after no more than 3 months of training, including flexibility and stability training. Technique training may be more successful if it follows a period of concentrated physical training. During the in-season, emphasis ought to be on maintaining ROM by effective implementation of stretching programs.